Incidence, demographics, and clinical characteristics of diabetes of the exocrine pancreas (type 3c): A retrospective cohort study - Woodmansey, C; McGovern, AP; McCullough, KA; Whyte, MB; Munro, NM; Correa, AC; Gatenby, PAC; Jones, SA; De Lusignan, S (American Diabetes Association, 2017)
This study was conducted to describe the incidence of diabetes following pancreatic disease, assess how these patients are classified by clinicians, and compare clinical characteristics with type 1 and type 2 diabetes.Primary care records in England (n = 2,360,631) were searched for incident cases of adult-onset diabetes between 1 January 2005 and 31 March 2016. We examined demographics, diabetes classification, glycemic control, and insulin use in those with and without pancreatic disease (subcategorized into acute pancreatitis or chronic pancreatic disease) before diabetes diagnosis. Regression analysis was used to control for baseline potential risk factors for poor glycemic control (HbA1c ≥7% [53 mmol/mol]) and insulin requirement.We identified 31,789 new diagnoses of adult-onset diabetes. Diabetes following pancreatic disease (2.59 [95% CI 2.38-2.81] per 100,000 person-years) was more common than type 1 diabetes (1.64 [1.47-1.82]; P < 0.001). The 559 cases of diabetes following pancreatic disease were mostly classified by clinicians as type 2 diabetes (87.8%) and uncommonly as diabetes of the exocrine pancreas (2.7%). Diabetes following pancreatic disease was diagnosed at a median age of 59 years and BMI of 29.2 kg/m2. Diabetes following pancreatic disease was associated with poor glycemic control (adjusted odds ratio, 1.7 [1.3-2.2]; P < 0.001) compared with type 2 diabetes. Insulin use within 5 years was 4.1% (3.8-4.4) with type 2 diabetes, 20.9% (14.6-28.9) with diabetes following acute pancreatitis, and 45.8% (34.2-57.9) with diabetes following chronic pancreatic disease.Diabetes of the exocrine pancreas is frequently labeled type 2 diabetes but has worse glycemic control and a markedly greater requirement for insulin.